EVOLUTION OF REPRESENTATIONS ON THE SPATIAL ORGANIZATION OF THE ECONOMY - F. Sharipov (Вестник университета)
The author reviewed the theories of spatial economics, the contribution of Russian scientists to the theory of spatial economic development and the development of development programs for the respective territories of the Russian Federation is generalized and systematized. The main features of the modern spatial economy of the Russian regions are formulated. The conclusion is made that it is necessary to define the country's long-term priorities in the sphere of Russia's social and economic development with due regard for the features of the modern spatial economy of the Russian regions when developing the Strategy of Spatial Development of the Russian Federation.